Reverse microemulsion mediated sol-gel synthesis of lithium silicate nanoparticles under ambient conditions: Scope for CO2 sequestration - Khomane, Ramdas B.; Sharma, B. K.; Saha, S.; Kulkarni, B. D. (Chemical Engineering Science, 2006)
We report on the synthesis of nanocrystalline lithium silicate by coupling of sol-gel method in reverse microemulsion. The sample calcined at 800 degrees C gives pure phase lithium metasilicate nanocrystallites. X-ray diffraction and transmission electron microscopy confirmed the formation of nanocrystalline lithium silicate particles with a narrow size distribution. The nanoparticle prepared in the microemulsion shows enhanced CO2 sorption capacity and shorter retention times at higher temperature (similar to 131 ml/g at STP at 610 degrees C which are better than the best known results. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; Carbon dioxide; Microemulsion; particle; separations; sol-gel; surfactant